PRODUCT DEVELOPMENT STRATEGY FOR HALAL FOOD AND BEVERAGES IN JABODETABEK - Fadilah, Taufik; Munawar, Wildan; Pangestu, R. Ali (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study aims to determine the product development strategy of halal food and beverages in Jabodetabek. This research method uses descriptive qualitative methods with a quantitative approach. The data analysis technique used is Analytical Network Process (ANP) which is for data collection through interviews and distributing questionnaires. The technique used in sampling is purposive sampling. The results of this study indicate that the strategies that need to be implemented are halal literacy programs to increase public awareness of the importance of halal products, free halal certification programs in resolving government policy barriers to expensive halal certification fees and coaching and training programs to improve the lack of education and training for less qualified human resources. The implications of this research are expected to have a positive impact on the halal food and beverage industry in Jabodetabek, improvements to halal certification policies and an increase in the competitiveness of halal products